(untitled) (Al-Academy, 2024)
The research was interested in studying the formal variations in the architecture of calligraphic structures, as the art of Arabic calligraphy and the art of Islamic architecture share a close relationship formed through the geometric feature and the standard ratio that controls the measurements of letters, as well as the characteristics that help it build and form letters and words in calligraphic structures bearing the geometric architectural character that It simulates the building and construction of buildings and architectural elements represented by domes, minarets, and arches, especially in the Kufic and Thuluth script. The research included four chapters. The first chapter dealt with the research problem, which posed the following question: (What are the formal variations in the architecture of linear structures?) The research aims to reveal the formal variations in the architecture Linear structures. The second chapter included the theoretical framework and previous studies and touched on the following topics: The first topic is the constructivism of architectural calligraphy, while the second topic is the computer and its role in processing lines. The third chapter includes research procedures that include following the descriptive approach (content analysis) in light of a research community that includes (42) forms. (4) samples were selected to represent the research sample based on the purposive selection method. The research tool (analysis form) was designed and presented to a group of experts to obtain validity and reliability and then analyze the sample. As for the fourth chapter, it contained the results, conclusions, recommendations and proposals